KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA SEMARANG DAN KOTA MAGELANG - Dwiki Soeryo Prabowo, 08.05.52.0172 (Students Journal of Accounting and Banking, 2013)
Receipts Revenue is a significant source of revenue for financing development in a routine and autonomous regions. The amount of local tax revenue components and levies greatly influenced by many types of local taxes and levies are applied and adapted to the regulations relating to the acceptance of these two components.This study analyzes the contribution of local taxes and levies to revenue in fiscal year 2009 to 2012. Contribution of local tax revenue and revenue gains levies to the City of Semarang and Magelang City Government within a period of Fiscal Year 2009 - 2012 is significant with an average contribution of local taxes amounted to 32.24 Semarang and Magelang in at 8.67 percent per year. While the average contribution levies percent of Semarang at 8.00 and 5.34 in Magelang In order to enhance the ability of local governments to implement regional autonomy, the central government set the Law No. 28 Year 2009 on Regional Taxes and Levies. The result in 2011 revenues increased PAD in Semarang City magelang 59.01 whereas increased only 6.72 percent from the previous year.To further enhance the contribution of local tax revenue and levies to total revenue receipts and government revenues as well as enlarge the city of Semarang and Magelang city government needs to be done collecting the types of local taxes and levies in accordance with Law No. 28 of 2009 to establish the basic Regulation as a voting rule local taxes and local levies as a source of revenueKeywords: source revenue, local taxes and levies